Research on the Nonlinear Absorption Coefficient of 98% Deuterated DKDP Crystal at Fourth-Harmonic-Generation Wavelength - Wu, Pengcheng; Zhang, Lisong; Xu, Mingxia; Liu, Baoan; Wei, Liening; Li, Yang; Chai, Xiangxu; Sun, Xun (Frontiers in Physics, 2022)
A series of 98% deuterated DKDP crystals were grown in solutions with different pD values (2.9, 3.3, 3.8, and 4.3) using the rapid growth method. Samples were cut along the z-direction and fourth-harmonic-generation (FHG) direction which contained both pyramidal and prismatic regions. The nonlinear absorption (NLA) coefficient β of 98% deuterated DKDP crystals was obtained using the Z-scan method operated at the FHG wavelength (266 nm) of a picosecond Nd:YAG laser. According to the results, the nonlinear absorption at 266 nm could be identified as two-photon absorption. The β values of crystal grown in the solution with 3.3 pD value were higher than those of crystals grown in solutions with other pD values under higher laser fluence. The results also indicated that FHG device samples should be prepared from the pyramidal region due to its lower β value. This work will help optimizing the application of 98% DKDP crystals as FHG elements in high-power laser systems.